Folklor w edukacji muzycznej – metoda projektów - Andrys , Magdalena (Studia Edukacyjne, 2020)
In times of prevailing mass pop-culture there is almost no space for traditions and customs connected with folklore. Educationalists and music teachers continue to pursue progressive methods demonstrating the artistic values of folklore. Project-based learning is a method which can be the beginning of forming an attitude of respect and cultivation of national heritage. This method may not only can develop social abilities, teach self-reliance and organization, but also create an opportunity to find interest even among most difficult problematic issues. A recent project ‘Muzyczna Kawaleriada z Uśmiechem – Regiony kulturowe Polski’ has already created a possibility for researching if the above method can be applied for musical education for grades 4-6. Folk culture, especially songs and dances, has become a subject of observation for teachers and at the same time an evaluation for students. A questionnaire was used for that purpose. All three stages of the project, preparation, realization and presentation as well as the results of conducted research show that project-based learning is an attractive and effective method of music education. Certain values of the beauty of Polish folk songs and dances are also indicated.